PENGARUH KUALITAS LAYANAN DAN CITRA MEREK (BRAND IMAGE) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Pipin Suryanisari; Sesi Lestari (Universitas La Tansa Mashiro, 2019)
This study is to determine the factors that influence Service Quality and Brand Image on Purchasing Decisions at PT. Akses Lintas Nusantara. The purpose of this study is to determine the Service Quality and Brand Image of the Purchasing Decision. The method used in this research is quantitative descriptive research method. The sampling technique used is the Incidental Sampling Technique, which is a sampling technique based on coincidence, meaning that anyone who accidentally or incidentally meets the researcher can be used as a sample, if it is deemed by chance that people meet it, it is suitable as a source of data. The sample in this study consisted of 100 respondents who met the criteria in this study. Data collection was carried out by distributing questionnaires (questionnaires), observation and library studies. Testing of this study was carried out using an instrument test that is a validity test and a reliability test, a classic assumption test that is a multicollinearity test, multiple linear regression analysis, a coefficient of determination test, a normality test, a correlation coefficient test. Hypothesis testing is t test (partial) and F test (simultaneous). The results showed there was a significant influence between service quality variables on purchasing decisions, t test results on service quality obtained tcount> ttable (5,211> 1,660). the results showed there was a significant influence between brand image variables on purchasing decisions, t test results on brand image obtained tcount> ttable (3.075> 1,660).F test results show Fcount of 18.504 with a significant 0,000 and Ftable of 2.70. Because the value of Fcount> Ftable = 18.504> 2.70, it can be concluded that simultaneously service quality variables X1 and brand image X2 have a significant effect on purchasing decision variables (Y).